(untitled) (Journal of Medical Sciences, 2018)
Sigmoid volvulus (SV) is an unusual condition in Libya, responsible for about 3-5% of all intestinal obstructions. SV is generally described as an illness in elderly patients, persons with psychiatric disorders, or persons living in nursing homes or mental institutions, multiple co-morbidities and an elongated mesosigmoid. The condition can be treated conservatively, but in the presence of fever, high WBC count, perforation, ischaemia and peritonitis, surgery is the best option. This report describes a case of a very large gangrenous sigmoid volvulus in a healthy 65-year-old male. A review of the diagnosis and management is subsequently described. Early identification and management are crucial in treating sigmoid volvulus before the appearance of gangrene, thereby avoiding further complications and associated mortality.